Marx & Moderne: Dialektik der Befreiung oder Paradoxien der Individualisierung? - Stadlinger, Jörg; Sauer, Dieter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2010)
This article discusses the use of “paradox” and “ambivalence” as key terms of social theory as suggested by modernization theories instead of the dialectical term “contradiction”. It is shown that the underlying assumption of these concepts – the “paradoxical force to freedom” – is based on questionable and not thought-out premises. In contrast, the use of Hegel’s dialectical idea of freedom and Marx’s Theory of Productive Forces offers a perspective in which “paradoxes” stated by the modernization theories can be conceptualised and in which the underlying changes can be identified as a momentum of a Dialectic of Liberation. The historical basis of the “Paradoxes of Individualization” are changes in the relation of autonomy and heteronomy related to the radical change in the organisation of work.